Java : - Schildt, Herbert (McGraw-Hill, 2007)
The definitive guide to Java has been fully expanded to cover every aspect of Java SE 6, the latest version of the world's most popular Web programming language. This comprehensive resource contains everything you need to develop, compile, debug, and run Java applications and applets.